Tree Diversity, Stand Structure, and Community Composition in an Island Forest of Pulau Perhentian Besar, Terengganu - Pardi, F; N Mohd Said, M; Ismail, A; J Sidik, N; A Radzun, K; N Ruziman, H; S Kasri, S (International Journal of Engineering and Technology, 2019)
The Perhentian Island Archipelago comprising of 11 small islands is located in the state of Terengganu are among the biodiversity rich localities in Peninsular Malaysia. Perhentian Besar with approximately 867 hectares is one of the inhabited island and become the centre of tourism besides Perhentian Kecil. Island is well known as a place for many endemic and endangered living organism as previously demonstrated on other similar forested islands in Southeast Asia. However, there is little attention and effort of protection has been received by the terrestrial ecosystems that reside nearby the coastal. Thus, the present study investigates on tree diversity, stand structure and community composition in the island of Perhentian Besar, Terengganu. Forest plot of 0.5 hectare was established to analyze the floristic composition of tree taxa. The plot was divided into 10 subplots of 25m x 20m. All trees with 5cm diameter breast height (dbh) and above were tagged, measured for dbh size, recorded and identified. Voucher specimens were taken for further verification purposes. A total of 102 tree species were recorded comprising of 28 families and 65 genera. Rubiaceae had the highest number of species (11 species) and with regards to relative dominance, Shorea leprosula (Dipterocarpaceae) gave the highest importance value index (IVi) for species with a value of 8.45%. The Shannon-Weiner Diversity Index (H’) was considered high in the present study with 3.94 (H’max = 4.62) and the Evenness Index (E) value of 0.85 indicated that all species in the present study are almost equally abundant. The forest stand structure had a reverse J-shaped curve for tree size-class distributions as frequently observed in many natural forests, which indicated that the forest stand in the study site had a good recruitment patterns and also a main feature of matured forest in Peninsular Malaysia. The present study will help us to understand the pattern of tree species composition, diversity and forest ecosystem dynamic in Pulau Perhentian Besar.